Analisis Pemilihan Cak Lontong sebagai Ketua Tim Sukses Pramono Anung - Rano Karno dalam Pilkada DKI Jakarta 2024 - Revalyza Misbah; Mega Arinda Pramessella; Zahra Hanifah Salma; Ismoyo Sekar Prastin; Tias Rahma Dewi; Abdul Ghofur (Jurnal Politik dan Pemerintahan Daerah, 2025)
The aim of this study is to examine the political strategy of the Indonesian Democratic Party of Struggle (PDI Perjuangan) in the 2024 Jakarta gubernatorial election (Pilkada DKI Jakarta) through the appointment of Cak Lontong as the campaign manager for the Pramono Anung – Rano Karno ticket. This research analyzes the selection of Cak Lontong, a public figure with an entertainment background, as part of a political campaign strategy. His appointment is particularly interesting to study as it reflects the phenomenon of celebrity involvement in electoral contests in Indonesia, especially in urban areas such as Jakarta. This study adopts a qualitative approach to gain an in-depth understanding of the strategic considerations behind PDI Perjuangan’s choice of Cak Lontong, as well as his role in shaping an inclusive, communicative, and community-oriented campaign image. The findings indicate that Cak Lontong’s selection was not solely based on his popularity as a comedian, but also influenced by other factors such as integrity, political communication skills, and educational background. With these various considerations, his appointment as campaign manager successfully created a campaign atmosphere that was relaxed yet meaningful, bridging the party’s political messages through a lighthearted and educational delivery style. This strategy reflects PDI Perjuangan’s adaptation to the political dynamics of urban areas, which require a more communicative approach while still maintaining leadership quality. This research shows that the combination of popularity and competence can enhance a political party’s competitiveness without compromising the substance of its political message. Therefore, this study recommends that similar strategies be considered by other political parties to engage voters more effectively.